Lightweight bamboo structures - Report on 2021 International Collaboration on Bamboo Construction - Dauletbek, Assima; Xue, Xin; Shen, Xinqi; Li, Haitao; Feng, Zixian; Lorenzo, Rodolfo; Liu, Kewei; Zea Escamilla, Edwin; Yao, Lianshu; Zheng, Xiaoyan (Sustainable structures, 2023)
2021 International Collaboration on Bamboo Construction was held from September 1 to December 1, 2021. The practice was held by the College of Civil Engineering of Nanjing Forestry University, University College London, International Bamboo and Rattan Organisation (INBAR) and co-organized by 6 international institutions and national companies of China. Two main bamboo structures were setup by the teachers and students in the campus of Nanjing Forestry University. More than 50 students attended the practice, including international students from different countries. The practice was held to deliver the feasibility and applicability of bamboo in various geometries and different spans, and different areas. Innovative technologies like BIM Revit Architecture and Sketchup were used for the design of bamboo structures. The main principle of the practice was that the raising of bamboo structures should be simple using a minimum of materials aside from bamboo. The results of the project contributed to the popularization of the use of bamboo in the architecture, engineering and construction sectors.